Problematic Procedural Issues of Preventing Criminal Offenses on Road Passenger Transport (Law and Safety, 2020)
The author has studied the state of activity of pre-trial investigation and inquiry agencies of the National Police of Ukraine and the Prosecutor’s Office on preventive activities in regard to establishing the causes and conditions that contributed to the commission of criminal offenses, including violations of traffic safety rules and operation of road passenger transport and necessary measures to eliminate them. The author has accomplished a comparative analysis of the current criminal procedural legislation and the provisions of the previous Criminal and Procedural Code of Ukraine of 1960 and the departmental regulatory base on the researched issue. The views of scholars and representatives of various scientific schools on the researched issues have been analyzed. As a result the author has formulated own scientific position on this matter. The author has studied the procedural mechanism of the algorithm of an investigator, interrogator and prosecutor’s actions on establishing the causes and conditions that contributed to the commission of a criminal offense and taking the necessary measures. Suggestions and recommendations for their legislative improvement have been provided, in particular, establishing the responsibilities of an investigator, interrogator and prosecutor in relation to preventive activities at the stage of pre-trial investigation. It has been offered to consider the submission as a form of eliminating the factors that contributed to the commission of criminal offenses.Based on the analysis of law enforcement activities of investigative units, inquiry agencies and prosecutor’s offices, as well as existing theoretical and doctrinal provisions of criminal procedure, the author has suggested propositions and recommendations for improving the theoretical part of criminal procedure, current criminal procedural legislation of Ukraine and interdepartmental and departmental regulatory acts.
Keywords: an investigator; an interrogator; road passenger transport; traffic accident; a criminal offense; criminal proceedings; legislation